THE IMPLEMENTATION OF THE VILLAGE FUND IN AN UNDERDEVELOPED VILLAGE: A CASE STUDY OF TENDE VILLAGE, GALANG SUB-DISTRICT, TOLITOLI REGENCY - Safar, Abdul Wahid; Dawai, Ahmad Syahrial Semen; Nursam, Nursam (J-3P (Jurnal Pembangunan Pemberdayaan Pemerintahan), 2024)
This study aims to explore the implementation of Village Fund management in Tende Village, Galang Sub-district, Tolitoli Regency, Central Sulawesi Province. This study employs qualitative research with a case study approach. The data collection techniques used were observation, in-depth interviews, and documentation from primary and secondary sources. This study discovered that the implementation of Village Fund at the planning level could accommodate community aspirations. Development in the infrastructure sector had a significant impact on the community. However, the negative side of Village Fund implementation is the dominance of the Activity Implementation Team (TPK), which does not involve the community in implementation, especially in infrastructure development. Furthermore, due to the limited bureaucracy, the disbursement of the Village Fund took a considerable amount of time. In addition, the Village Fund had implications for decreasing the social capital of village communities. This study argues that the utilization of Village Fund should be tailored to the specific conditions of each village. This study contributes by providing additional perspectives on Village Fund implementation in underdeveloped villages.